Islamic Bioethics in the Twenty-First Century: with Mohammed Ghaly, “Islamic Bioethics in the Twenty-first Century”; Henk ten Have, “Global Bioethics: Transnational Experiences and Islamic Bioethics”; Amel Alghrani, “Womb Transplantation and the Interplay of Islam and the West”; Shoaib A. Rasheed and Aasim I. Padela, “The Interplay between Religious Leaders and Organ Donation among Muslims”; Aasim I. Padela, “Islamic Verdicts in Health Policy Discourse: Porcine-Based Vaccines as a Case Study”; Mohammed Ghaly, “Collective Religio-Scientific Discussions on Islam and HIV/AIDS: I. Biomedical Scientists”; Ayman Shabana, “Law and Ethics in Islamic Bioethics: Nonmaleficence in Islamic Paternity Regulations”; and Willem B. Drees, “Islam and Bioethics in the Context of ‘Religion and Science’.” - Ghaly, Mohammed (Zygon, 2013)
Islamic bioethics is in good health, this article argues. During the twentieth century, academic researchers had to deal with a number of difficulties including the scarcity of available Islamic sources. However, the twenty-first century witnessed significant breakthroughs in the field of Islamic bioethics. A growing number of normative works authored by Muslim religious scholars and studies conducted by academic researchers have been published. This nascent field also proved to be appealing for research-funding institutions in the Muslim world and also in the West, such as the Qatar National Research Fund (QNRF) and the Netherlands Organization for Scientific Research (NWO). On the other hand, the article argues that contemporary Islamic bioethics is in need of addressing news issues and adopting new approaches for the sake of maintaining and improving this good health in the future.